“If Things Really Go On as They Are at the Moment, Then I Will Work Illegally. End of Story.” Pandemic Realities in Marginalized Entrepreneurships - Tümpel, Markus; Cardone, Pia (Qualitative Sociology Review, 2022)
Micro-enterprises and self-employed individuals have been hit particularly hard by the economic effects of the COVID-19 pandemic, but few studies have tackled the issue. This paper is based on four in-depth case studies of self-employed people from different sectors who have been greatly affected by measures taken to control the pandemic. By capturing shifts in the perception of institutional and economic pressures, as well as precarity after the outbreak of COVID-19, we gained profound insight into crisis management among entrepreneurs working in niche or marginalized fields of business. We found parallels in their biographies and attitudes, but their perceptions of the COVID-19 pandemic differ. We observed paradoxes and hybrid logic, as well as different ways of coping with the crisis. Having a “plan B” helped in some cases, while all of them benefitted from the solidarity of networks and communities.